2023
DOI: 10.1007/s00348-023-03633-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between shadow imaging and in-line holography for measuring droplet size distributions

Abstract: A direct comparison of the droplet size and number measurements using in-line holography and shadow imaging is presented in three dynamically evolving laboratory scale experiments. The two experimental techniques and image processing algorithms used to measure droplet number and radii are described in detail. Droplet radii as low as $$r = 14$$ r = 14  µm are measured using in-line holography and $$… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…During droplet evaporation, the morphology changes, encompassing alterations in physical and chemical properties, such as surface tension, contact angle, and contact radius. Due to the short coherence length of LED, current holographic measurement techniques for droplet morphology often employ the method of coaxial phase-shifting recording. , However, coaxial systems can solely measure stationary objects or slowly change dynamic processes. In this regard, the off-axis holography developed in this study is better suited for capturing the rapid changes in the dynamic evaporation process of droplets.…”
Section: Resultsmentioning
confidence: 99%
“…During droplet evaporation, the morphology changes, encompassing alterations in physical and chemical properties, such as surface tension, contact angle, and contact radius. Due to the short coherence length of LED, current holographic measurement techniques for droplet morphology often employ the method of coaxial phase-shifting recording. , However, coaxial systems can solely measure stationary objects or slowly change dynamic processes. In this regard, the off-axis holography developed in this study is better suited for capturing the rapid changes in the dynamic evaporation process of droplets.…”
Section: Resultsmentioning
confidence: 99%
“…The curves are a bit noisy but generally indicate an increasing droplet number with increasing breaker strength at diameters above approximately 400 µm, the curves converge at smaller diameters. A number of authors have measured droplet diameter distributions in breaking wave and wind wave systems in the laboratory (see for example Veron et al 2012;Ortiz-Suslow et al 2016;Erinin et al 2022;Ramirez de la Torre et al 2022), the field (Wu et al 1984;Monahan 1968) and in DNSs with and without wind (Wang et al 2016;Tang et al 2017;Mostert et al 2022). Many of the distributions in these studies are either fitted or compared with separate power-law functions at small and large droplet diameter ranges.…”
Section: Droplet Diameter Distributionsmentioning
confidence: 99%
“…Veron et al (2012) studied spray generation at high wind speeds (31.3-47.1 m s −1 ) and found that the numbers of large droplets exceeded theoretical predictions. More recently, Erinin et al (2022) measured droplet speed and acceleration statistics of spray generated at wind speeds up to 12 m s −1 in a wind wave field in a laboratory tank and reported on droplet speed and acceleration probability density functions. The authors found droplets with speeds greater than the measured wind speed.…”
mentioning
confidence: 99%